Role of Neurotropic B Vitamins in the Treatment of Diabetic Neuropathy: Narrative Review - Narmin Essa; Mohammed Aladul (University of Mosul, 2022)
Diabetic neuropathy (DN) is the presence of signs and symptoms that are suggestive of neuropathy in diabetic patients, after excluding other possible causes of nerve damage. Diabetic neuropathy and its complications affect the quality of life, sleep patterns, and daily activities of the patient. Up to date no FDA-approved reversing treatment was found. Studies showed that neurotropic B vitamins (vitamin B1, B6 and B12) had an important role in nerve regeneration and included in prescriptions of DN. However, these vitamins were not included in the guidelines of DN management. The aim of this review is to explore the role of neurotropic B vitamins in the treatment of DN including the mechanism of action and the evidence supporting their use. Review of the literature revealed many clinical trials examining the effect of these vitamins (alone or combined) for DN. These vitamins and/or their derivatives had well-illustrated disease-modifying mechanisms on DN. However, larger randomized clinical trials for longer periods are needed to approve their use in DN and to be included in national and international guidelines. This was hindered by the fact that vitamins are non-patentable and therefore fewer funds would be allocated for large randomized clinical trials.